Comparison study on efficacy of UNICEF specified therapeutic food (F-75/F-100) with traditionally used home based food in management of severe acute malnutrition - Shukla, Anand; Rao, Y. K. (International Journal of Contemporary Pediatrics, 2018)
Background: The management of malnutrition depends on its severity. While mild to moderate malnutrition can be managed on ambulatory basis, severe malnutrition is preferably managed in hospital settings. This study was undertaken to find the magnitude of SAM in children (6 months to 60 months) and to compare the UNICEF specified therapeutic food (F-75/F-100) with traditionally used home based food in treatment of severe acute malnutrition. Methods: This prospective and observational study was conducted in the Department of Pediatrics of G.S.V.M. Medical College, L.L.R. and Associated Hospitals, Kanpur. Logarithmic transformation was achieved by SPSS 20. Results: The prevalence of SAM in children between 6 months to 60 months of age to be 18%. Clinical spectrum of SAM showed 95.24% of marasmus 3.57% of Kwashiorkor and 1.19% of marasmic kwashiorkor. There was significant increase in weight of hospitalized patient receiving F75/F100 at 28 days of follow up. Weight gain was not statistically significant in patients treated at home. Conclusions: SAM should preferably be treated in hospital with appropriate therapy rather than home based management.